Prevalence of iron deficiency anaemia among microcytic anaemic premenopausal patients at tertiary care hospital, Karachi - Memon, Ghulam Abbas; Khan, Tooba Jawed; Abbas, Shabnam; Shaikh, Ghulam Abbas; Shah, Nusrat; Kayani, Hammad Afzal; Habib, Muhammad Atif (International Journal Of Community Medicine And Public Health, 2020)
Background: Iron deficiency anaemia (IDA) is the prevalent form of anaemia which has become a major public health problem, globally. Women in the reproductive age group (15–49 years of age) are at increased risk, especially in the South Asian population. It is of paramount importance to identify these micronutrient deficiencies in this age group as it adversely affects the birth outcomes, but the mother and the child at risk of morbidity and mortality during pregnancy. Methods: A cross-sectional study was conducted at Civil Hospital, Karachi for 12 months i.e. October, 2018 to December, 2019. Data was prospectively collected from patients after obtaining written informed consent. 377 patients were included who met the diagnostic criteria. Descriptive statistics were used and qualitative data analysis; mean, standard deviation, frequency, and percentages were respectively calculated. Effect modifiers were controlled through stratification to see the effect of these on the outcome variable. For post-stratification, the chi-square test was applied with a p value of≤0.05. Results: A total of 377 patients with microcytic anaemia were enrolled from Civil Hospital, Karachi. Mean age, duration of anaemia, haemoglobin, height, weight and BMI in our study was 29.28±6.14 years, 1.41±0.26 months, 9.27±0.86 mg/dl, 26.72±1.56 kg/m2, 138±7.28 cm and 78.7±9.87 kg. Out of 377 patients with microcytic anaemia, 144 (38.2%) and 233 (61.8%) had and did not have iron deficiency anaemia. Conclusions: IDA is frequently found in microcytic anaemia patients. Thus, it is important to screen premenopausal in female patients for iron deficiency presenting with microcytic anaemia to prevent adverse outcomes.